Optimal Placement of SVC Using Fuzzy and Firefly Algorithm - P.SURESH BABU; P.B. CHENNAIAH; M. SREEHARI (Institute of Advanced Engineering and Science, 2015)
Voltage stability is major phenomena in any power system network for reliability and continuity operation. But the tight operation of power system due to overloading or fault on the system which is evitable and major threat to the power system. So it is necessary to maintain the voltages within the constraints at the overloading conditions also by placing of Static VAR Compensator (SVC) at optimal locations. New approaches are used to find the placement and size of the SVC at different locations. Fuzzy is used to find the location and the size of the SVC is fined by the Firefly algorithm. This paper considers different loading conditions of the power system network (125,150,175over loading conditions). From the results we can conclude that the power losses are reduced and the voltages can be maintained within the limits .IEEE 14 bus, IEEE 30 bus system is taken for the implementing the above techniques.